2020
DOI: 10.1177/1091581820907324
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Compound-Related Effects on Coagulability in Rats and Cynomolgus and Rhesus Monkeys by Thrombin Generation Kinetic Measurement

Abstract: Thrombin generation assay (TGA) is a sensitive method for the assessment of the global clotting potential of plasma. This kinetic assay can detect both hypocoagulable and hypercoagulable conditions: delayed or reduced thrombin generation leading to a prolonged clotting time, or induced thrombin activity, shifting the coagulation cascade toward thrombosis. The purpose of this study is to qualify the TGA in nonhuman primates (NHP) and rats for its use during nonclinical in vivo and in vitro studies. Blood was dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…Regardless of the differences outlined above, our Chacma baboon ETPs are still more similar to human ETPs than pig, rabbit 9 , Sprague–Dawley rat, and Cynomolgus monkey ( Macaca fascicularis ) 10 , ETPs are. Siller-Matula et al 9 , after performing TGAs on six members of each species using a similar method to ours, report median ETPs of 2043 nM.minute on pigs and 6295 nM.minute on rabbits, which represents differences of − 52% and + 49%, respectively, from the corresponding human median of 4235 nM.minute.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Regardless of the differences outlined above, our Chacma baboon ETPs are still more similar to human ETPs than pig, rabbit 9 , Sprague–Dawley rat, and Cynomolgus monkey ( Macaca fascicularis ) 10 , ETPs are. Siller-Matula et al 9 , after performing TGAs on six members of each species using a similar method to ours, report median ETPs of 2043 nM.minute on pigs and 6295 nM.minute on rabbits, which represents differences of − 52% and + 49%, respectively, from the corresponding human median of 4235 nM.minute.…”
Section: Discussionmentioning
confidence: 69%
“…Poitout-Belissent et al 10 investigated compound-related effects on coagulability in Sprague–Dawley rats, and Cynomolgus and Rhesus monkeys, using a TGA method similar to ours, and report baseline mean values for the rats and rhesus monkeys used in their experiments, which can be used for indirect comparison. The mean ETP of 664.3 nM.minute reported for rats is 84% lower than the median ETP reported for humans by Siller-Matula et al 9 , who reported a much higher median ETP for the same rat species (3075 nM.minute, which represents a difference of only − 27% from the human median), highlighting the large interindividual variation possibly present in rats, which may also complicate the use of this species in coagulation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is a limited amount of studies that compare TG between various species [ 8 , 10 , 15 , 16 ]. When interspecies differences were evaluated [ 9 , 17 , 18 , 19 ], the authors suggested that while some animals might have TG similar to humans, others might not. This type of data can bring useful evidence forward for coagulation investigations that are species specific.…”
Section: Introductionmentioning
confidence: 99%